Intenção de uso de preservativos entre mulheres jovens e adultas - Carvalho, Michelle Alves de (2019)
Introduction: The female susceptibility to HIV comes from several factors, and it is important to emphasize the dissymmetry of roles between the sexes, especially in the family environment, making the woman subject to the wishes of her partner, which reverberates in the abandonment of the use of condoms, despite knowing the risks involved in this conduct. Objective: To evaluate the behavioral intention of condom use and its determinants among young and adult women. Method: A cross-sectional, comparative, cross-sectional, quantitative approach based on Theory of Reasoned Action, performed in a family health unit, with 142 women aged 18 to 40 years, between August and October 2017, using the instrument Intent of Condom Use (IUPres). The analysis was performed using Pearson's rcorrelations and Stepwise multiple regression, using the software Statistical Package for the Social Sciences, version 21. The research was approved under protocol n. 0442/16 and CAAE 58597416.3.0000.5188. Results: Young women are more likely to use condoms ( = 3.35) when compared to adults. As an explanatory factor of behavioral intention in both groups, the normative beliefs were highlighted because they explain in more than 85% the intention to use condoms. When checking the influence of external variables, self-care was evidenced as an explanatory factor of 86.3% of the behavioral intention in the group of youngsters, whereas in the adult group, both normative beliefs, self-care and trust in the other explained together with 86.2%, the latter with negative weight, that is, as the confidence in the partner increases, the intention to use condoms decreases. Conclusion: The use of Theory of Reasoned Action made it possible to elucidate that young and adult women had low behavioral intentions related to the use of condoms. It was found, therefore, that both groups conjecture that normative beliefs, self-care and confidence in the partner interfere in the decision to use condoms.